PENGARUH PENURUNAN HARGA KARET MENTAH TERHADAP DAYA BELI MASYARAKAT DI PASAR DESA PASIR JAYA - Jannah, Wirdatul; 'Aini, Yulfita; -, Hidayat (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This research was conducted Â to analyze the effect go down price of raw rubber to power of buy society at traditional market in Pasir Jaya Village. This research was conducted using quantitative data, data collection in this study using a questionnaire containing 20 grains of questions and distributed to 85 respondents who had income from the sell of raw rubber. The sampling technique that researchers do that is to use the formula slovin. Analysis of data used in this study is to test hypotheses using validity and reliability testing.Â The results of the regression analysis indicate there is a very strong and significant correlation between go down price of raw rubber with power of buy society at traditional market in Pasir Jaya Village that is equal to 0.529 or by 52,9 %. Researcher is recommended to society at Pasir jaya Village to be more high the quality of the raw rubber so that the power of sale the raw rubber have a high level or the society must have a side job so that the society have a other income.